Technical Characteristics and Development Trend of Printed Circuit Heat Exchanger Applied in Floating Liquefied Natural Gas - Xie, Liyi; Zhuang, Dawei; Li, Zhiqiang; Ding, Guoliang (Frontiers in Energy Research, 2022)
The printed circuit heat exchanger with high efficiency, good compactness and reliability, presents potential application in the floating liquefied natural gas platform. This paper offers a review on technical characteristics and development trend of printed circuit heat exchanger applied in floating liquefied natural gas, including the development state of printed circuit heat exchangers, the application state of printed circuit heat exchangers in floating liquefied natural gas and the key issues for potential application of printed circuit heat exchangers in floating liquefied natural gas. Firstly, the existing research results of heat transfer and pressure drop characteristics of printed circuit heat exchangers with various flow channels are analyzed, and the correlations of the heat transfer coefficients and the pressure drop of these flow channels are summarized. Then, the application state of printed circuit heat exchangers in floating liquefied natural gas is introduced, and the functions of printed circuit heat exchanger used in the existing floating liquefied natural gas facilities are analyzed. Finally, the key issues for applying printed circuit heat exchangers in floating liquefied natural gas, including the structure design criteria, influence mechanism of sloshing conditions on performance, and methods of suppressing the adverse effects of sloshing conditions are proposed. It is indicated that the present studies focus on the effect of single sloshing motion on the thermal-hydraulic performances of printed circuit heat exchangers, but few attention has been paid onto the coupling effects of multiple sloshing motions which conform more closely to the actual operation conditions of printed circuit heat exchangers in floating liquefied natural gas. Thus the future work should be aim at the influence mechanisms and structure optimizations in terms of thermal-hydraulic performance under multiple sloshing conditions.